Prevention strategies for blood‐borne viruses—in the Era of vaccines, direct acting antivirals and antiretroviral therapy. (17th May 2016) - Pfaender, Stephanie; von Hahn, Thomas; Steinmann, Joerg; Ciesek, Sandra; Steinmann, Eike
Summary: Blood‐borne viruses, such as hepatitis B virus, hepatitis C virus, human immunodeficiency virus, and the facultative blood‐borne hepatitis E virus, are considered a major public health problem given that they are accountable for millions of deaths each year. Treatment options, including effective vaccine design, development of antiviral strategies and the implementation of antiretroviral therapy have improved substantially over the last couple of years and contribute to successful treatment and prevention of these infectious diseases. In this review, we summarise the current knowledge and concepts in prevention of transmission of these blood‐borne viruses.